Advanced Motorcycle Riding Simulation: a Case Study of Sleep Deprivation Effects on Motorcyclist Muscle Fatigue - Rashid, Helmi; Salwa Ahmad, Anis; Rahman Omar, Abdul; Muhammad Syahmi Wan Fauzi, Wan; Halim Abdullah, Abdul; Hanif Ahmad Hamidi, Shahfuan (International Journal of Engineering and Technology, 2018)
In enabling scientific studies on motorcycling, a full-scale ergonomic and adjustable motorcycle simulator, Postura MotergoTM was developed at the METAL laboratory, Faculty of Mechanical Engineering, Universiti Teknologi MARA, Malaysia. A case study was conducted using the simulator to simulate prolonged motorcycle riding simulation along with a wireless surface electromyography (sEMG) device to monitor the respondentâ€™s muscle activities. The aim was to investigate the effects of sleep deprivation amongst motorcyclist during prolonged motorcycle riding. It involved five (5) male respondents aged 23 years with a normal BMI and several years of motorcycling experience with one (1) respondent amongst them was sleep-deprived. They were required to ride the simulator for a maximum period of 2-hours non-stop. Seven (7) bilateral muscle groups were monitored throughout the simulations. It concluded that the muscles start to fatigue at a much earlier time significantly compared to other respondents that was mainly caused by sleep deprivation.Â Â